Hubungan Pola Makan Dan Aktivitas Fisik Dengan Risiko Terjadinya Diabetes Melitus Pada Remaja Di SMP Negeri 1 Sukosari Kabupaten Bondowoso - Ummah, Nabila Khoirotul; Suprajitno; Marsaid; Hidayah, Nurul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: To determine the relationship between diet and physical activity with the risk of developing diabetes mellitus in adolescents at SMP Negeri 1 Sukosari Bondowoso District. Methods: This research design uses a non-experimental quantitative descriptive method with a cross sectional approach. The study population was 146 adolescents at risk of diabetes mellitus. The sampling technique uses cluster random sampling. The research sample was 60 teenagers at risk of diabetes mellitus. Results: The results of the Spearman Rank test showed that eating patterns with the risk of diabetes mellitus in adolescents had a p value of 0.004, while physical activity with a risk of diabetes mellitus in adolescents had a p value of 0.003. Conclusion: The conclusion of this research was that there was a relationship between diet and physical activity and the risk of developing diabetes mellitus in adolescents at SMP Negeri 1 Sukosari, Bondowoso Regency. So it is hoped that health workers can provide education to teenagers to improve their diet and maintain physical activity.